Routine online activities and vulnerability to dating app facilitated sexual violence - Wolbers, Heather (Trends & issues in crime and criminal justice, 2024)
This study examines factors associated with dating app facilitated sexual violence (DAFSV) among a large, nationally representative sample of dating app or website users (n=9,987). Through the lens of routine activity theory, we examined the way in which respondents used dating platforms and how this was associated with experiences of DAFSV. Prolific dating platform users and those who share more information, who chat with people on different platforms or who paid for an online dating service were more likely to report experiencing DAFSV. Risk factors for DAFSV extending from the online sphere into the physical world were also explored. Findings give much needed context for experiences of DAFSV and provide direction for responses aimed at protecting individuals from harm facilitated by online dating platforms.